The Development Direction of Undergraduate Tourism Management Major under the Guidance of Party Building - Chen, Hongying; Fu, Sheng; Liu, Ping (Journal of Theory and Practice of Social Science, 2024)
The International College of Tourism is one of the construction units of the high-level vocational colleges with Chinese characteristics and the high-level professional group construction project (the "Double High Project"), and the tourism management professional group is one of the two high-level professional groups with Chinese characteristics that are mainly created by the construction of the "Double Universities". And party building is an important force in leading universities to carry out education and teaching work and promoting education and teaching management. The core professional tourism management construction of the Double High Professional Group is firmly rooted and steadily advancing under the guidance of party building. Let all faculty and staff make long-term plans, provide suggestions and suggestions for the development of the college, ensure the steady progress of education and teaching in the college, promote the professional development of tourism management teachers, and ensure that the level of education and training ability can be greatly improved. Clarify the guiding ideology, goals, requirements, and key tasks of party building work in universities, and regard high-quality party building as the core of tourism management construction in the dual high professional group, in order to explore the progress of tourism management under the guidance of party building.